Serial Paediatrics Omics Tracking in Myalgic Encephalomyelitis (SPOT-ME): protocol paper for a multidisciplinary, observational study of clinical and biological markers of paediatric myalgic encephalomyelitis/chronic fatigue syndrome in Australian adolescents aged 12–19 years - Adam Scheinberg; Natalie Thomas; Katherine Huang; Paul R Gooley; Elisha K Josev; Tracey Chau; Darcy Tantanis; Sarah J Knight; Christopher W Armstrong (BMJ Open)
Introduction Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a disabling condition that can affect adolescents during a vulnerable period of development. The underlying biological mechanisms for ME/CFS remain unclear and have rarely been investigated in the adolescent population, despite this period representing an age peak in the overall incidence. The primary objective of this is to provide a foundational set of biological data on adolescent ME/CFS patients. Data generated will be compared with controls and over several time points within each patient to potentially develop a biomarker signature of the disease, identify subsets or clusters of patients, and to unveil the pathomechanisms of the disease.Methods and analysis This protocol paper outlines a comprehensive, multilevel, longitudinal, observational study in paediatric ME/CFS. ME/CFS patients aged 12–19 years and controls will donate biosamples of urine, blood, and peripheral blood mononuclear cells for an in-depth omics profiling analysis (whole-genome sequencing, metabolomics and quantitative proteomics) while being assessed by gold-standard clinical and neuropsychological measures. ME/CFS patients will then be provided with a take-home kit that enables them to collect urine and blood microsamples during an average day and during days when they are experiencing postexertional malaise. The longitudinal repeated-measures study design is optimal for studying heterogeneous chronic diseases like ME/CFS as it can detect subtle changes, control for individual differences, enhance precision and boost statistical power. The outcomes of this research have the potential to identify biomarker signatures, aid in understanding the underlying mechanisms, and ultimately, improve the lives of children with ME/CFS.Ethics and dissemination This project was approved by the Royal Children’s Hospital’s Human Research Ethics Committee (HREC 74175). Findings from this study will be disseminated through peer-reviewed journal publications and presentations at relevant conferences. All participants will be provided with a summary of the study’s findings once the project is completed.